2009
DOI: 10.1111/j.1439-037x.2008.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Yield Criteria for Drought and Heat Resistance in Chickpea (Cicer arietinum L.)

Abstract: The chickpea (Cicer arietinum L.) is usually grown under rainfed, rather than irrigated conditions, where drought accompanied by heat stress is a major growth constraint. The aim of this study was to select chickpea genotypes having resistance to drought/heat stress and to identify the most appropriate selection criteria for this. A total of 377 chickpea accessions were sown 2 months later than normal for the Antalya region (Turkey) to increase their exposure to the drought and high‐temperature conditions of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 35 publications
3
65
2
Order By: Relevance
“…Biological yield could be accepted as the most valuable characteristicamong the traits.Biological yield had the highest direct effect on grain yield (Table 3)and biological yield could be increasedvia straw yield, branches per plant andpods per peduncle. The biological yield in chickpeawas found to be the most important selection criteria for the contributing grain yield due to the highest and the positive direct effect (Canci and Toker, 2009). The more branches per plant resulted in the more pods per plant.…”
Section: Resultsmentioning
confidence: 99%
“…Biological yield could be accepted as the most valuable characteristicamong the traits.Biological yield had the highest direct effect on grain yield (Table 3)and biological yield could be increasedvia straw yield, branches per plant andpods per peduncle. The biological yield in chickpeawas found to be the most important selection criteria for the contributing grain yield due to the highest and the positive direct effect (Canci and Toker, 2009). The more branches per plant resulted in the more pods per plant.…”
Section: Resultsmentioning
confidence: 99%
“…Delaying the planting by 2 months compared to normal in the Mediterranean climate resulted in successful identification of heat-tolerant genotypes [84]. Several heat-tolerant genotypes were identified from screening of 377 germplasm accessions.…”
Section: Genetic Variability For Heat Tolerancementioning
confidence: 99%
“…Aslam et al (2008) evaluated the performance of 23 chickpea genotypes and reported significant variation in morphological, physiological, phonological characters and yield and yield components. In case of breeding drought and heat-resistant chickpea days to the first flowering and maturity should be evaluated ahead of many other phenological traits, harvest index, biological yield and pods per plant to escape terminal drought and heat stresses for increased yield (Canci and Tokar, 2009) Karadavut et al (2010) studied the some fababean genotypes across the environments and reported significant variation in yield among genotypes and also over environments. Khan et al (2010) studies genetic variability and correlation in wheat under water stress conditions.…”
Section: Introductionmentioning
confidence: 99%